On bubbles in cryptocurrency prices - Maarten R. C. van Oordt (Tinbergen Institute, 2024)
This paper investigates how cryptocurrencies relate to concepts such as bubbles, Ponzi-schemes and digital gold in a tractable model for cryptocurrency prices. Investors in the baseline equilibrium hold coins to sell them at a profit to future users if they anticipate in increase in transactional demand per coin. Investors in a bubble equilibrium hold the cryptocurrency because they expect its price to appreciate merely due to future investment inflows. Investors who participate in a bubble equilibrium for a cryptocurrency with non-negative money growth experience Ponzi-scheme equivalent payoffs in the aggregate. The net investment inflows required to sustain a bubble equilibrium are smaller for cryptocurrencies with less new issuance, a lower level of transactional demand and higher growth in transactional demand. Cryptocurrencies with negative issuance (e.g., that burn transaction fees) may generate positive aggregate cash flows to investors even if their price path follows a bubble trajectory.
Keywords: E51; F31; G1; 330; Asset pricing; Bitcoin; crypto-asset; exchange rates; rational bubble